The collective consumption network. Issue 6 (4th November 2014) - Närvänen, Elina; Gummesson, Evert; Kuusela, Hannu
Abstract : Purpose: – The purpose of this paper is to introduce a network perspective to the study of collective consumption. The authors examine the characteristics of heterogeneous consumption collectives formed around a Finnish footwear brand. The case is both theoretically and practically relevant. It differs from previous research by featuring consumer grassroot activities, face-to-face interaction and strong pre-existing social relationships. Design/methodology/approach: – Qualitative case study research was conducted with different methods of data generation including interviews, participant observation and cultural materials such as newspaper articles and photos. Findings: – A new concept of collective consumption network is introduced. Five kinds of consumption collectives are identified, including place focussed, brand focussed, activity focussed, idea focussed and social relations focussed consumption collectives. The strength of ties as well as the role of the brand varies within the collectives. Practical implications: – Suppliers should find an appropriate network position, where they can enable and support shared value creation. Developing skills to identify and cultivate weak links as well as mobilize resources are important. Originality/value: – The findings illustrate the heterogeneity and complexity of collective consumption. In particular, the paper discusses the way self-organizing and emergent consumption collectives and the supplier interact and integrate resources within the network.